Rethinking the "Innovator´s Dilemma" : does intrapreneurship solve start-up threats to incumbents : the case of Siemens? - Eckhardt, Hannah (2020)
Christensen’s Innovator's Dilemma thesis describes the paradoxical phenomenon that large companies become victims of their own success. Companies are successful and market leaders by virtue of having a large customer base and market share, but innovation takes root in small niche customer demographics. So, listening to their customers' needs causes companies to fail because they cannot implement the disruption associated with the next significant market innovation. However, Christensen published his theory at a time when companies were reliant on internal innovation. Since 2003, the phenomenon of open innovation described by Henry Chesbrough, has taken hold. The open innovation model is based on a company using its surrounding ecosystem, collaborating with partners such as start-ups, academic institutions or customers, in order to enable innovation. In recent years there has been a dramatic change in the relationship between corporations and start-ups. Where in the past incumbent corporations had the upper hand, today start-ups often dominate. A significant advantage of start-ups compared to incumbents is that the former can easily reach niche markets. To mitigate start-up advantages, corporations have begun to invest in intrapreneurial activities. This gives companies opportunities to become innovative while also meeting current customer needs. One company that have recognized the importance of intrapreneurial activities is Siemens. This thesis examines whether intrapreneurship and associated innovation strategies have solved the innovator's dilemma for Siemens and whether Siemens can protect itself from startup threats.